BCLC™ NAD⁺ Supplement System Targeting SIRT1: A Time-Sequential Biphasic NMN-Resveratrol-Quercetin Formulation with Supporting Clinical and Pharmacological Evidence - Ziraoui, Nour-Eddine; Salazar, Mateo; Kensington, Alexander (International Journal of Public Health and Medical Research, 2026)
Background: Age-associated decline in NAD+ is closely linked to reduced SIRT1 activity and impaired metabolic resilience. The disclosed BCLC™ system combines NMN, trans-resveratrol, quercetin, piperine, and trimethylglycine within a time-sequential biphasic release architecture. Objective: We retained the disclosed composition, formulation parameters, figures, and performance data, and further matched them with published human and mechanistic evidence relevant to the system modules. Methods: We summarized the disclosed active-component window, release design, and in-vitro endpoints, and compared them with peer-reviewed studies on NMN, resveratrol, quercetin, piperine, methyl-donor metabolism, and cyclodextrin-based solubility engineering. Results: The disclosed system outperformed a conventional comparator in reported cell and dissolution endpoints, including 4.1-5.5-fold SIRT1-pathway activation, 95.6-98.8% nicotinamide clearance, >=36-48 h intracellular NAD+ maintenance, and markedly improved 15-min dissolution of resveratrol, quercetin, and piperine. Published human studies consistently showed that NMN raises blood NAD+ and is generally well tolerated, while resveratrol displayed context-dependent metabolic and SIRT1-related effects and quercetin showed selective cardiometabolic and insulin-sensitivity benefits. Human evidence supporting piperine and methyl-donor support was indirect but mechanistically relevant. Conclusion: We consider the disclosed BCLC™ architecture biologically plausible and better supported than a simple mixed formulation.